High Order WKB Prediction of the Energy Splitting in the Symmetric Double Well Potential - Robnik, Marko; Salasnich, Luca; Vraničar, Marko (Progress of theoretical physics. Supplement, 2000)
The accuracy of the WKB approximation when predicting the energy splitting of bound states in a double well potential is the main subject of this paper. The splitting of almost degenerate energy levels below the top of the barrier results from the tunneling and is thus supposed to be exponentially small. By using the standard WKB quantization we deduce an analytical formula for the energy splitting, which is the usual Landau formula with additional quantum corrections. We also examine the accuracy of our and Landau formula numerically for the case of the symmetric double well quartic potential.